Introduction to statistical methods for biosurveillance : with an emphasis on syndromic surveillance - Fricker, Ronald D., Jr., 1960- (Cambridge University Press, 2013)
Presents basic and advanced methods with a focus on demonstrated added value for a broad class of public health surveillance problems.